Model development of isopropanol dehydration from binary and ternary mixtures with pervaporation: Comparison and environmental evaluation of hybrid separation methods - Huyen Trang Do Thi; Eniko Haaz; Andras Jozsef Toth (Results in Engineering)
This study investigates the separation of isopropanol (IPA) from water and ethanol (EtOH) using hybrid distillation-hydrophilic pervaporation (D+HPV), distillation-hydrophilic pervaporation-distillation (D+HPV+D), and distillation-hydrophilic pervaporation-distillation-heat integration (D+HPV+D+HI) systems. The pervaporation performance of PERVAP™ 1510 and PERVAP™ 4100 hydrophilic membranes is evaluated for ternary (IPA-EtOH-Water) and binary (IPA-Water) mixtures at varying feed compositions and temperatures. The results show that increasing the water content in the feed solution enhances permeate flux but decreases the separation factor and selectivity. The highest total flux, separation factor and selectivity values achieved during the investigations are 1.96 kg/m2h, 4785 and 1614 in the case of ternary mixture. The relevant values are, as follows 2.84 kg/m2h, 5780 and 6872 for IPA-Water experiments. Additionally, isopropanol exhibits a higher permeation ability than ethanol, increasing fluxes at higher IPA concentrations. Two pervaporation models (Model I and Model II) were used for parameter estimation, with Model II more accurately predicting flux behaviour, as it accounts for concentration-dependent diffusion coefficients. Regarding costs, D+HPV+D+HI offers the most balanced solution, with the lowest Total Annual Cost (TAC) of 275,000 €/year. A life cycle assessment (LCA) demonstrates that the D+HPV+D method has the highest environmental impact, with 0.392 kg CO2-eq. There is no significant difference in carbon emissions between the three methods when switching from fossil fuels to renewable energy, which can reduce emissions by 35 %, 34 %, and 30 % when using biofuels, solar, and wind energy, respectively. The study concludes that hybrid distillation-pervaporation systems are highly efficient, offering cost-effective and environmentally sustainable solutions for IPA dehydration. Furthermore, the improved Model II, which was first used for ternary mixture case, highlights that precise calculation of process simulations requires improving model accuracy.